(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This study explores consumer perception and behavioral response to rural FMCG marketing strategies in Nagpur District, India. With the growing importance of rural markets in the FMCG sector, the research investigates the effectiveness of marketing strategies involving product, price, promotion, and distribution in shaping consumer behavior. A descriptive research design was adopted, using a structured questionnaire to collect primary data from 100 rural consumers. The findings indicate that rural consumers prioritize product affordability and trust, with a strong preference for branded products in smaller packaging. Traditional promotional strategies, such as regional-language advertisements and free samples, were found to be more effective than digital promotions in influencing purchasing decisions. Furthermore, the study highlights the significance of local distribution channels like kirana stores and weekly markets, and identifies the role of income and education in shaping consumer preferences. The research provides valuable insights for FMCG companies to develop targeted, localized marketing strategies that cater to the specific needs of rural consumers, fostering brand loyalty and increasing market penetration.